2015
DOI: 10.1002/pmic.201500253
|View full text |Cite
|
Sign up to set email alerts
|

Integration of RNA‐seq and proteomics data with genomics for improved genome annotation in Apicomplexan parasites

Abstract: While high quality genomic sequence data is available for many pathogenic organisms, the corresponding gene annotations are often plagued with inaccuracies that can hinder research that utilizes such genomic data. Experimental validation of gene models is clearly crucial in improving such gene annotations; the field of proteogenomics is an emerging area of research wherein proteomic data is applied to testing and improving genetic models. Krishna et al [Proteomics 2015, 00, 1–11] investigated whether incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We actually speculate that N. caninum may activate a distinct subunit of p38 MAPK, since the other biological phenotypes assessed were distinct than that induced by NcLiv_GRA24 or PRU. Previous studies reported about some surface genes and secreted proteins, which are known to control virulence and host interactions in T. gondii infection, are altered in Neospora genome with different expression and functionality, which imply that there have been significant changes in the evolution of host-interacting genes between these species ( Reid et al, 2012 ; Ramaprasad et al, 2015 ; Silmon de Monerri and Weiss, 2015 ). Hence, the pursuit for such antigenic targets with potential p38 activation is desired and should be better investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We actually speculate that N. caninum may activate a distinct subunit of p38 MAPK, since the other biological phenotypes assessed were distinct than that induced by NcLiv_GRA24 or PRU. Previous studies reported about some surface genes and secreted proteins, which are known to control virulence and host interactions in T. gondii infection, are altered in Neospora genome with different expression and functionality, which imply that there have been significant changes in the evolution of host-interacting genes between these species ( Reid et al, 2012 ; Ramaprasad et al, 2015 ; Silmon de Monerri and Weiss, 2015 ). Hence, the pursuit for such antigenic targets with potential p38 activation is desired and should be better investigated.…”
Section: Discussionmentioning
confidence: 99%
“…SAGs are the principal surface antigens of E. tenella , and encoding a single domain of membrane binding proteins tethered by glycosylphosphatidylinositol (GPI)-anchors to the surface of invasive sporozoites and merozoites [20]. Most SAGs were expressed in the second-generation merozoites in a time dependent fashion, which might be related to host cell adhesion, but their specific biological functions are still unclear [12, 21, 22]. The invasion of sporozoites of E. tenella could also be inhibited significantly by interaction with Et SAG1 monoclonal antibody 2H10E3 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing errors carried over from the assembly to the annotation process might create artificial amino acid mutations or insert stop codons in ORFs, shortening existing or creating non-expressed peptides. Proteomics experiments are vital in experimentally validating gene models originating from transcriptome assemblies by comparing the expressed/measured peptides with the in silico database, as described in [ 36 , 37 ]. However, functional annotation can frequently deal with an inaccurate ORF as long as most of the true coding region is retained.…”
Section: Functional Annotations Using Generic Tools and Ad mentioning
confidence: 99%